2017
DOI: 10.1128/iai.01060-16
|View full text |Cite|
|
Sign up to set email alerts
|

Mucosal Antibodies to the C Terminus of Toxin A Prevent Colonization of Clostridium difficile

Abstract: Mucosal immunity is considered important for protection against Clostridium difficile infection (CDI). We show that in hamsters immunized with Bacillus subtilis spores expressing a carboxy-terminal segment (TcdA 26 -39 ) of C. difficile toxin A, no colonization occurs in protected animals when challenged with C. difficile strain 630. In contrast, animals immunized with toxoids showed no protection and remained fully colonized. Along with neutralizing toxins, antibodies to TcdA 26 -39 (but not to toxoids), whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…In each case expression had been achieved by fusion to a B. subtilis gene encoding a surface-expressed spore coat protein (either CotB or CotC). The proteins chosen included the following: (i) VP26 and VP28, both envelope proteins of the shrimp virus WSSV that when displayed on recombinant B. subtilis spores and incorporated in feed have been shown to confer protection to shrimp challenged with WSSV (7-9); (ii) a protein consisting of a C-terminal domain of Clostridium difficile toxin A (TcdA 26 -39 ) that, when expressed on the spore surface, has been shown to confer protection from C. difficile infection (CDI) in hamsters dosed orally with these recombinant spores (4,27); (iii) streptavidin (SA) that, when expressed on spores, can be conjugated to the monoclonal antibody cetuximab, enabling targeting to colon cancer cells (15); (iv) two enzymes, subtilisin E (AprE), an alkaline protease, and alpha-amylase (AmyE), which are both enzymes of industrial importance and commonly incorporated in animal feed (28,29).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In each case expression had been achieved by fusion to a B. subtilis gene encoding a surface-expressed spore coat protein (either CotB or CotC). The proteins chosen included the following: (i) VP26 and VP28, both envelope proteins of the shrimp virus WSSV that when displayed on recombinant B. subtilis spores and incorporated in feed have been shown to confer protection to shrimp challenged with WSSV (7-9); (ii) a protein consisting of a C-terminal domain of Clostridium difficile toxin A (TcdA 26 -39 ) that, when expressed on the spore surface, has been shown to confer protection from C. difficile infection (CDI) in hamsters dosed orally with these recombinant spores (4,27); (iii) streptavidin (SA) that, when expressed on spores, can be conjugated to the monoclonal antibody cetuximab, enabling targeting to colon cancer cells (15); (iv) two enzymes, subtilisin E (AprE), an alkaline protease, and alpha-amylase (AmyE), which are both enzymes of industrial importance and commonly incorporated in animal feed (28,29).…”
Section: Resultsmentioning
confidence: 99%
“…As vaccines we used SH14 spores that express the TcdA 26 -39 antigen of C. difficile fused to two spore coat protein anchors, CotB and CotC. SH14 is equivalent to strain PP108 that has previously been shown to confer protection against C. difficile infection (CDI) in murine and hamster models of infection (4,27). We immunized mice with spores of SH14 and PP108 using oral administration, and after a total of four doses, we measured TcdA 26 -39 -specific IgG (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although TcdA- and TcdB-specific Ab could arguably result in a population of asymptomatic but infectious individuals, immunogens that stimulate these responses could be very useful as a first generation vaccine. It should be noted that Hong and co-authors recently observed that oral vaccines consisting of B. subtilis expressing TcdA fragments induced TcdA-reactive mucosal Abs that cross-reacted with the vegetative cell surface and spore coat of C. difficile and limited colonization [6]. This work suggests that selection of toxin-derived vaccine epitopes that stimulate cross-reactivity against the C. difficile bacterium could be promising.…”
Section: Vaccine Candidates and Constraints On Adaptive Immunity To Themmentioning
confidence: 88%
“…Mucosal delivery of recombinant spores Whilst systemically generated anti-toxin responses reduce or eliminate toxin-associated symptoms, activation of mucosal responses at the immediate site of infection may reduce symptoms through the prevention of toxin action within the gut. One approach that has shown preclinical success is the oral delivery of recombinant B. subtilis spores expressing fragments of TcdA, which limited colonisation and disease in hamsters [77]. Further protection was associated with high levels of toxin specific sIgA in the faeces of these animals highlighting the importance of mucosal response in protection.…”
Section: Spore Coat Proteins As Vaccine Candidatesmentioning
confidence: 99%